2007
DOI: 10.1007/s00234-007-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute bilateral basal ganglia lesions in diabetic uraemia: diffusion-weighted MRI

Abstract: A syndrome associated with acute bilateral basal ganglia lesions in diabetic uraemic patients is rare, with reversible changes demonstrated by clinical and imaging findings. DWI showed that the bilateral basal ganglia lesions in this syndrome were primarily vasogenic in origin, although there were small foci of cytotoxic oedema within the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 21 publications
5
60
1
5
Order By: Relevance
“…Our patient did not have hypotension, vasculitis or an active infection. Bilateral basal ganglia involvement may also occur in nonketotic hyperglycemia and it is observed as hyperdense lesions in cranial computed tomography (5). There was no significant hyperglycemia at the hospitalization of our patient and blood glucose levels were regulated during hospitalization with adjustment of insulin doses.…”
Section: Conclusıonsmentioning
confidence: 54%
See 1 more Smart Citation
“…Our patient did not have hypotension, vasculitis or an active infection. Bilateral basal ganglia involvement may also occur in nonketotic hyperglycemia and it is observed as hyperdense lesions in cranial computed tomography (5). There was no significant hyperglycemia at the hospitalization of our patient and blood glucose levels were regulated during hospitalization with adjustment of insulin doses.…”
Section: Conclusıonsmentioning
confidence: 54%
“…The patients should be carefully assessed about dialysis sufficiency and acid-base and electrolyte abnormalities. reFerences involvement is not frequent (3)(4)(5). Acute movement disorder accompanied by bilateral basal ganglia involvement in patients with diabetic uremia is a separate clinical syndrome (3).…”
Section: Conclusıonsmentioning
confidence: 99%
“…Üremik hastalarda simetrik bazal ganglion lezyonuna bağlı ani gelişen hareket bozukluğu nadir olarak görülen bir klinik tablodur 4 . Bu vakamızda ani olarak başlayan konuşma bozukluğu olan ve koreiform hareketleri olan hastaya klinik ve görüntüleme yöntemleri ile diyabetik üremik ensefalopati tanısı konulmuştur.…”
Section: Introductionunclassified
“…Hegde et al 35 showed bilateral basal ganglia lesions in a 37-year-old HIVseropositive male with central nervous system toxoplasmosis by MRI. Lee et al 36 found that there was abnormality in bilateral basal ganglia in diabetic uremic patient by DWI. However, there are no contradictions between our study and their studies, [34][35][36] because our objects and the former research objects were different.…”
mentioning
confidence: 98%
“…However, many scholars [34][35][36] showed that there was abnormality in bilateral basal ganglia in some patients. Corti et al 34 found that there was abnormality in bilateral basal ganglia in patients with AIDS with central nervous system cryptococcosis.…”
mentioning
confidence: 99%